Ecosystem feedbacks and cascade processes: understanding their role in the responses of Arctic and alpine ecosystems to environmental change. - Wookey, P.A.; Aerts, R.; Bardgett, R.D.; Pabtist, F.; Brathen, K.A.; Cornelissen, J.H.C.; Gough, L.; Hartley, I.P.; Hopkins, D.W.; Lavorel, S.; Shaver, G.R. (Global Change Biology, 2009)
Global environmental change, related to climate change and the deposition of airborne N-containing contaminants, has already resulted in shifts in plant community composition among plant functional types in Arctic and temperate alpine regions. In this paper, we review how key ecosystem processes will be altered by these transformations, the complex biological cascades and feedbacks that might result, and some of the potential broader consequences for the earth system. Firstly, we consider how patterns of growth and allocation, and nutrient uptake, will be altered by the shifts in plant dominance. The ways in which these changes may disproportionately affect the consumer communities, and rates of decomposition, are then discussed. We show that the occurrence of a broad spectrum of plant growth forms in these regions (from cryptogams to deciduous and evergreen dwarf shrubs, graminoids and forbs), together with hypothesized low functional redundancy, will mean that shifts in plant dominance result in a complex series of biotic cascades, couplings and feedbacks which are supplemental to the direct responses of ecosystem components to the primary global change drivers. The nature of these complex interactions is highlighted using the example of the climate-driven increase in shrub cover in low-Arctic tundra, and the contrasting transformations in plant functional composition in mid-latitude alpine systems. Finally, the potential effects of the transformations on ecosystem properties and processes that link with the earth system are reviewed. We conclude that the effects of global change on these ecosystems, and potential climate-change feedbacks, cannot be predicted from simple empirical relationships between processes and driving variables. Rather, the effects of changes in species distributions and dominances on key ecosystem processes and properties must also be considered, based upon best estimates of the trajectories of key transformations, their magnitude and rates of change. © Journal compilation © 2009 ...